A New Algorithm of Mobile Node Localization Based on RSSI - Zhang, Jie; Liu, Hongli; Huang, Bowei (Scientific Research Publishing, 2011)
Position mobile node coordinate is a key component to determine the accuracy and efficiency of positioning in wireless sensor networks. Flexible location algorithm admits to adjust the accuracy and time cost of positioning based on the users references. This paper develops a location algorithm named Signal Strengthening Dynamic Value (SSDV) based on the database of RSSI to position the mobile node in terms of the value of beacon nodes RSSI. The proposed algorithm has successfully improved the accuracy of mobile nodes positioning and real-time, and simulation results show high performance in effectiveness of the algorithm.
Keywords: RSSI; Wireless Sensor Networks; Mobile Location Position; Signal Strength; Weight